IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY IN SEMARANG CITY - Sigit Irianto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Research of social responsibility of companies in the city of Semarang is a research about the activities of the company as a partner of the Government and people in building the environment and the society. Implementation of corporate social responsibility attached to the values of the local wisdom. Article 74 of Act Number 40 of 2007 about Limited Liability Company and Government Regulation Number 47 Year 2012 about Social and Environmental Responsibility of Limited Liability Company has been set up corporate social responsibility as a part of the company's activities. The substance of corporate social responsibility is not only in the aspect of physical development, but also the empowerment of local communities. Semarang City Government has been managing corporate social responsibility with the funding through Gardu Kempling Program; this program isan Integrated Movement in Health, Economics, Education, Infrastructure, and Environment. Management of corporate social responsibility is used mostly to assist poverty reduction programs. The process of implementation of corporate social responsibility is accepted by the Semarang Regional Secretariat Cooperation Section. The company's understanding of the basis for the laws governing corporate social responsibility, most informants do not know the exact rules and regulations of governing the provision of corporate social responsibility. The focus of corporate social responsibility is to improve the quality of life until it finally emerged establishment communities to address social problems.